Pengembangan Majalah Keberagaman Budaya (MABEDA) Berbasis Kearifan Lokal Pamekasan pada Materi IPAS Bab 6 Topik A Kelas IV SDN Durbuk 1 - Ningrum, Irma Wahyu; Fauziah, Humairah (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research is motivated by the lack of a availability of teaching materials at SDN Durbuk 1 especially in learning IPAS, so that it becomes one of the obstacles for teachers in the learning process. In this case, digital technology has a positive impact on overcoming the limitations of these teaching materials through interactive magazines. This study aims to develop an interactive magazine on the diversity of Pamekasan culture based on local wisdom that can support learning activities. This study used a research and development (R&D) method with the ADDIE model. The subjects of this study were grade IV students of SDN Durbuk 1. The data collection techniques used were through interviews, observation, and questionnaries to determine the effectiveness of the magazine product. The results by learning material experts obtaining a score of 92%, learning media experts obtaining a score of 96%, and language experts with a score of 94% and the product trial were obtained from the results of student responses obtaining a score 98% with a very good category. Based on the results of the data analysis, the cultural diversity magazine is very suitable for use in the learning process.